MENDIDIK ANAK DENGAN CINTA - Salami, Salami (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2018)
The true love of the mother to her children is no doubt. The mother is always ready to grow up the children, to feed them, and to serve them from the early child until they be became teenager. However some times, the mother thought that she loves the children in every activity she does in their relationship, in fact the children do not fell that the mother loves them. This can be caused by different perception of the children and the mother to understand the language of love. In this article will be explain how important is to understand the language of love to make the same perception between the children and the mother. As a result the mother loves the children and the children feel that they are loved.